High School Private Vocational School Learning in West Kalimantan During Physical Distancing COVID-19 in 2020 - Aloysius Mering (STKIP Singkawang, 2021)
This study aims to reveal information about the implementation , to overcome obstacles , and the effectiveness of online learning at Senior High Schools (SMA / SMK) in West Kalimantan during Physical Distancing Covid-19 Year 202 0 . I nformation obtained s urvei purposively in nine SMA / SMK (including six elementary schools and four secondary school) in K abupaten Bengkayang, Ketapang, Hedgehog, Melawi, and Sintang West Kalimantan. Respondent teachers were 137 people.The questions that were given to respondents in detail were about the effectiveness of online learning, the media , the resources used, the obstacles faced, and the efforts to overcome these obstacles. The results of descriptive analysis of the teacher's response revealed that the